Efektivitas Kombinasi Jus Belimbing dan Pepaya Terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi: The Effectiveness of a Combination of Starfruit and Papaya Juice in Reducing Blood Pressure in Elderly People with Hypertension - Hasanah, Uswatun (Dohara POAJ, 2025)
Introduction: Hypertension is a condition where the systolic blood pressure is more than 140 mmHg and the diastolic pressure is more than 90 mmHg. The aging process leads to a decline in physical and mental abilities. As they age, the elderly often experience various organ disorders and chronic diseases. One of the most common chronic diseases is hypertension. Aging itself is a process that cannot be avoided. Therapy is done by using a combination of star fruit and papaya juice to reduce hypertension. The purpose of knowing the effectiveness of the combination of star fruit and papaya juice on lowering blood pressure in elderly people with hypertension. Methods: This study uses a quantitative approach using experimental methods. The population in this study were elderly people in RT 08/RW 07 Sangkuriang hamlet, East Ogan Komering Ulu, South Sumatra in 2024, as many as 30 respondents. The sample in this study were 25 respondents. The sampling technique used purposive sampling. This research instrument uses Standard Operating Procedures (SOP) and observation sheets. Tests carried out using the Paired T-Test test. Results: The results of systolic blood pressure showed that the p-value of 0.000 means P <0,05 and diastolic blood pressure showed that the p-value of 0,000 means P <0,05. Discussion: The effectiveness of the combination of star fruit and papaya juice on reducing systolic and diastolic blood pressure in elderly people with hypertension.